From form to function: the role of Nox4 in the cardiovascular system - Chen, Feng; Haigh, Stephen; Barman, Scott A.; Fulton, David (Frontiers in Physiology, 2012)
The NADPH oxidase (Nox) family of proteins is comprised of seven members, including Noxes1–5 and the Duoxes 1 and 2. Nox4 is readily distinguished from the other Nox isoforms by its high level of expression in cardiovascular tissues and unique enzymatic properties. Nox4 is constitutively active and the amount of reactive oxygen species (ROS) contributed by Nox4 is primarily regulated at the transcriptional level although there is recent evidence for post-translational control. Nox4 emits a different pattern of ROS and its subcellular localizations, tissue distribution and influence over signaling pathways is different from the other Nox enzymes. Previous investigations have revealed that Nox4 is involved in oxygen sensing, vasomotor control, cellular proliferation, differentiation, migration, apoptosis, senescence, fibrosis, and angiogenesis. Elevated expression of Nox4 has been reported in a number of cardiovascular diseases, including atherosclerosis, pulmonary fibrosis, and hypertension, cardiac failure and ischemic stroke. However, many important questions remain regarding the functional significance of Nox4 in health and disease, including the role of Nox4 subcellular localization and its downstream targets. The goal of this review is to summarize the recent literature on the genetic and enzymatic regulation, subcellular localization, signaling pathways, and the role of Nox4 in cardiovascular disease states.